Effectiveness of the PRECEDE-PROCEED model for improving the care knowledge, skill, and sense of competence in mothers of preterm infants - Shaoli Li; Shufang Liu; Xinchun Zhang; Yali Chen; Xiaohong Ren (Journal of International Medical Research, 2022)
Objective This quasi-randomized controlled trial was performed to evaluate the effects of the PRECEDE-PROCEED model (PPM) in enabling mothers of preterm infants to develop care knowledge, skill, and a sense of competence. Methods Among 116 mothers of preterm infants, 60 received traditional discharge education (control group) and 56 received PPM discharge education (PPM group). Improvement in knowledge and skills was transformed into the mothers’ routine daily care of infants. The primary outcome was knowledge of preterm infant care. The secondary outcomes were preterm infant care skills and a sense of competence, routine intervention compliance among mothers, and the readmission rate of infants 6 months after discharge. Results Six months after discharge, the mean knowledge score and mean skills score were significantly higher in the PPM group than in the control group. The mothers’ sense of competence with respect to both self-efficacy and satisfaction was also significantly better in the PPM group than in the control group. Moreover, intervention behavior compliance and the readmission rate were significantly better in the PPM group than in the control group. Conclusion Care knowledge, skills, and sense of competence in mothers of preterm infants improved after implementation of the PPM.